Securitization of Climate Change in the Arctic - The Case of Iceland. - Ingólfsdóttir, Auður (2011)
Audur Ingólfsdóttir, University of Iceland & University of Lapland, Finland at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.